The Quality of School Climate and Teachers"™ Classroom Communication Skills as Predictors of Pupils"™ Performance in Nigeria - Sopekan, Sarah Oludola; Owieadolo, Ngozi Rita (International Journal of Learning and Instruction (IJLI), 2023)
This study examined the quality of school climate and teachers"™ classrooms communication skills as predictors of pupils"™ performance in Lagos State, Nigeria. Correlational survey research design was used for the study. The sample comprised 120 teachers who were selected from 30 primary schools. Multi-Stage sampling technique was used for the selection.  Two validated self-designed instruments were used to collect data for the study. The first one was titled"Observational Schedule on School Climate and Teachers Communication Skills (OSSCTCS). The second one was an achievement test titled" Pupil"™s Achievement Test (PAT) which was used to collect data on the performance of the pupils involved in the study. OSSCTCS  was subjected to a reliability test through inter-rater scale technique and it yielded a reliability coefficient of 0.82.While Kuder-Richardson 20 formula was used to determine the reliability of the achievement test. It yielded reliability index of 0.91.Data collected were analysed using inferential statistics of multiple regression. Findings from the study revealed that there was significant composite contribution of school climate and teachers"™ communication skills to pupil"™s performance (F(6,113)  = 4.744; p0.05). Again, school climate had the highest significant relative contribution to pupils"™ performance (Î² = .504; t = 7.741; p0.05) andit is followed by teachers"™ communication skills which had the least non-significant relative contribution (Î² = .015; t = .349; p0.05). Based on the findings of the study, it was recommended that training programs, seminars or workshops should be organised by experts in the field of early childhood education to train school heads and teachers on the importance of aesthetically designed early childhood schools. Also, that teachers should be trained on the significant of effective communication.